CURRENT ISSUES AND OPTIONS FOR HORMONAL CONTRACEPTION IN ADOLESCENTS AND YOUNG ADULT WOMEN WITH SICKLE CELL DISEASE: AN UPDATE FOR HEALTH CARE PROFESSIONALS - Vincenzo De Sanctis (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Abstract. Women with sickle cell disease (SCD) are of particular concern due to the significantly increased risk of pregnancy-related morbidity, mortality, and adverse outcomes. They have limited knowledge of the risks of pregnancy and childbirth as well as of the benefits and risks from the use of contraceptives. Thus, there is urgent need for appropriate information about reproductive family planning to reduce unintended pregnancy. Any decision regarding the use of contraceptives has to be based on the efficacy and the risks and benefits of the method used. Both the World Health Organization (WHO) and the Center for Disease Control and Prevention (CDC) have developed, published, and updated evidence-based guidelines for medical providers for the use of contraceptives in patients with specific medical chronic conditions. This article provides an overview of the present knowledge for the use of contraceptives in women with SCD. We believe that the collaboration between health care professionals (hematologists, obstetricians, endocrinologists, and primary care providers) can play a major role in identifying the safer contraceptive method to abolish the risks of unintended pregnancy and preserve the health status of patients with SCD.